Low birth weight associates with hippocampal gene expression. (24th March 2016) - Buschdorf, J.P.; Ong, M.L.; Ong, S.X.; MacIsaac, J.L.; Chng, K.; Kobor, M.S.; Meaney, M.J.; Holbrook, J.D.
Highlights: We compared hippocampal gene expression and DNA methylation between low and normal birth weight neonates. Birth weight associated with genome-wide transcription in the hippocampus. Differentially expressed genes were involved in neuronal projection. Few genes with differential expression co-varied with DNA methylation levels. Birth weight associates with hippocampal gene expression with a small epigenetic underpinning. Abstract: Birth weight predicts the lifetime risk for psychopathology suggesting that the quality of fetal development influences the predisposition for mental disorders. The connectivity and synaptic network of the hippocampus are implicated in depression, schizophrenia and anxiety. We thus examined the underlying molecular adaptations in the hippocampus as a function of the fetal conditions associated with low birth weight. We used tissues from the non-human primate, Macaca fascicularis, to identify changes in hippocampal gene expression early in postnatal development associated with naturally occurring low compared with normal birth weight. Microarrays were used to analyze gene expression and DNA methylation in the hippocampus of five low- and five normal-birth weight neonates. Real-time PCR was employed to validate differentially expressed genes. Birth weight associated with altered global transcription in the hippocampus. Hierarchical clustering of gene expression profiles from 24, 154 probe sets grouped all samples except one by their birth weight status. Differentially expressed genes were enriched in biological processes associated with neuronal projection, positive regulation of transcription and apoptosis. About 4% of the genes with differential expression co-varied with DNA methylation levels. The data suggest that low birth weight is closely associated with hippocampal gene expression with a small epigenetic underpinning by DNA methylation in neonates. The data also provide a potential molecular basis for the developmental origin of an enhanced risk for mental disorders.